TRANSPARANSI PELAYANAN ADMINISTRATIF DI KANTOR KELURAHAN UNER KECAMATAN KAWANGKOAN UTARA - Suoth, Marvela Berlian; Lengkong, Florence Daicy; Londa, Very (JURNAL ADMINISTRASI PUBLIK, 2017)
Abstract As a neighborhood, in a pattern of providing much-needed administrative services of openness (transparency) service to the community, where as the Government wards in the tasks and functions should provide administrative services to the community particularly in the making of a recommendation letter family card in this case have been set forth in a government regulation of the Republic of Indonesia Number 73 year 2005 about wards where the duties and functions of the village government apparatus must provide adsministrasi services to the community of openness so that the ministries can be a maximum of , as seen from the indicator of openness expressed by Dwiyanto (2006:242) which has an indicator regarding information disclosure requirements-pesrsyaratan, cost in the management of the Administration and the openness of the process of settlement/period required and in the theory of transparency expressed by the Mardiasmo in the Kristianten (2006:45), which mentioned the transparency is openness of the Government in providing information related to the activities of the management of public resources to those who need the IE community. Purpose in writing this is divided into two to qualify as needed in order to holds a Bachelor and other purposes i.e. to know the problems raised in this thesis. This research is descriptive research with qualitative approach. Data analysis technique used is a data analysis technique of the model of data i.e. Huberman & Miles reduction, data display and drawing conclusion/verification. Based on the research results obtained that can be seen is still the lack of openness of Government wards against requirements, costs and time in the management of the administration which caused the service to the community did not go well, as is still the lack of supporting facilities in the management of the Administration, and the formation of a national structure is not complete. Because of it's peneiti neighborhood suggested that the Government should be more open in providing service to the community, and there should be supporting facilities complete formation service and fill in the structure of national order for service to the community can be run well.Keywords: Transparency Of Administrative Services